2015
DOI: 10.5301/ejo.5000630
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Pit Morphology Evaluation during Optical Biometry Measurements using a Full-Eye-Length Swept-Source OCT Scan Biometer Prototype

Abstract: Compared with SD-OCT, resolution of the 1 mm retinal B scan of SS-OCT scan biometry was lower. However, advanced pathologic characteristics were clearly discernible. Repeatability and accuracy of CRT measurements were acceptable though lower than with the standard SD-OCT technique. The CRT differed significantly in eyes of particular interest (group I) between both devices. The new scan could provide useful information for subsequent patient examination and further treatment planning for cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Further analysis in Bertelmann et al . 8 study revealed a diagnostic advantage of the IOLMaster 700 in the detection of macular alterations during the preoperative biometrical measurements, especially for ERM, FTMH as well as IRF. Although data on different macular pathologies were reported, none sensitivity and specificity analysis for each alteration have been assessed in that study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Further analysis in Bertelmann et al . 8 study revealed a diagnostic advantage of the IOLMaster 700 in the detection of macular alterations during the preoperative biometrical measurements, especially for ERM, FTMH as well as IRF. Although data on different macular pathologies were reported, none sensitivity and specificity analysis for each alteration have been assessed in that study.…”
Section: Discussionmentioning
confidence: 88%
“…Bertelmann et al . 8 for the first time evaluated the foveal pit morphology during optical biometer measurements using the full-eye-length SS-OCT scan biometer. In this prospective study, 146 eyes were classified into two groups: phakic, non-vitrectomized eyes scheduled for cataract surgery and pseudophakic non-vitrectomized eyes with acrylic lenses.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that SS-OCT is able to better identify the choroidoscleral junction as compared to conventional spectral-domain OCT (SD-OCT) (8). Furthermore, when compared with SD-OCT, SS-OCT was shown to have better repeatability and accuracy of measurements (9).…”
Section: Introductionmentioning
confidence: 99%
“…Bertelmann et al ( 15 ) first evaluated the repeatability and precision of the central retinal thickness measured by SS-OCT compared to SD-OCT, which revealed the feasibility of optical biometer with SS-OCT as a macular disease screening method. Two studies had evaluated the value of using SS-OCT for the detection of macular disease, and one study further demonstrated that compared to fundus biomicroscopy, SS-OCT significantly improved the detection of macular disease in cataract patients ( 10 ).…”
Section: Discussionmentioning
confidence: 99%